MENGEMBANGKAN KEMAMPUAN BAHASA ANAK MELALUI KEGIATAN BERMAIN PERAN DI PAUD AZZAHRA - Ardiyansyah , Ahmad (LPPM STAI DARUSSALAM LAMPUNG, 2021)
Abstract Abstract: The ability of teachers to manage role playing learning is one of the attractions of children who can affect children's language skills. The purpose of this study is to describe the implementation of the role playing center, the role of the teacher, and the process of language learning through the technique of using an early childhood role playing center. The research method is descriptive-qualitative. Data collection techniques such as interviews, observation, and documents. The findings obtained include preparing a role playing learning plan, role playing activities require the full involvement of children, especially in the space and time of its application and the role of the teacher in building creative learning to improve children's language skills. This study concluded that the process of developing language skills in children is not enough to be done only once in the role playing learning center. Instead, it needs to be done repeatedly in the process of applying it by determining the themes in learning center playing roles differently. Thus, the role of the teacher is very important in building creativity in managing learning in the classroom.